2018
DOI: 10.3389/fmicb.2018.02157
|View full text |Cite
|
Sign up to set email alerts
|

Promising Antibiofilm Activity of Peptidomimetics

Abstract: Pathogenic biofilms are a global health care concern, as they can cause extensive antibiotic resistance, morbidity, mortality, and thereby substantial economic loss. Scientific efforts have been made over the past few decades, but so far there is no effective treatment targeting the bacteria in biofilms. Antimicrobial peptidomimetics have been proposed as promising potential anti-biofilm agents. Indeed, these structurally enhanced molecules can mimic the action of peptides but are not susceptible to proteolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…43,[58][59][60] Recent literature reviews have shown that peptides and peptidomimetics from different sources have been investigated for their prominent antibiofilm activity. [61][62][63][64][65] There are no previous studies demonstrating a relationship between 2S sulfur-rich seed storage (2SS) proteins or peptides and antibiofilm activity. To the best of our knowledge, this is the first scientific report using Capsicum natural peptides as antibiofilm and antiadhesive agents, herein called red pepper coat.…”
Section: Discussionmentioning
confidence: 99%
“…43,[58][59][60] Recent literature reviews have shown that peptides and peptidomimetics from different sources have been investigated for their prominent antibiofilm activity. [61][62][63][64][65] There are no previous studies demonstrating a relationship between 2S sulfur-rich seed storage (2SS) proteins or peptides and antibiofilm activity. To the best of our knowledge, this is the first scientific report using Capsicum natural peptides as antibiofilm and antiadhesive agents, herein called red pepper coat.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptidomimetics are synthetic molecules derived from (or inspired by) natural AMPs that mimic or reproduce their physicochemical properties (cationic charge, hydrophobicity, amphiphilicity) and biological effects [8,9]. Nevertheless, peptidomimetics often exhibit a higher bioavailability and a longer half-life in vivo [5] and many of them are more resistant to protease degradation [10].…”
Section: The Improved Biological Properties Of Peptidomimeticsmentioning
confidence: 99%
“…Design features that discriminate such anti-biofilm peptides are different from those mediating activity against planktonic cells (de la Fuente-Núñez et al, 2014;Haney et al, 2018a). Thus, antibiofilm peptides are an attractive class of molecules that can be further optimized through rational design (see below) or synthesis of peptidomimetics (Gomes Von Borowski et al, 2018).…”
Section: The Stringent Responsementioning
confidence: 99%